Influence of tidal regime, diurnal phase, habitat and season on feeding of an intertidal crab - Bas, Claudia Cristina (2013)
The relationship between diet and feeding activity of intertidal crabs, and environmental cycles (tidal, daily and seasonal), habitat and level of the intertidal zone (high/low) was studied using Neohelice granulata (Brachyura, Varunidae) as a model. This is a semi-terrestrial burrowing crab occupying different habitats in the Southwestern Atlantic coasts and estuaries from bare low intertidal mudflats to high intertidal salt marshes, and from fine, organic matter rich sediment to very coarse sediment with low content of organic matter. The study was carried out in two contrasting habitats of three sites with diverse sets of physical and biological conditions. Diet and feeding of adult N. granulata were indirectly studied through the proportion of food items and the presence/ absence of food in crab stomachs, respectively. This species has a dual mode of feeding: predominantly herbivorous (live plants or plant litter in salt marshes) or deposit feeder (superficial sediment and detritus in mudflats), but the quantity and quality of ingested food varies among habitats and sites. A trend to omnivory (including algae and conspecifics) was detected in relation to low quality of resources. Feeding activity modulated by a complex interaction of factors varied according to spatial and/or temporal changes in some natural cycles. Males and non-ovigerous females fed preferably after dark and during submersion periods, but also after emersion periods if mudflat sediment remained wet; salt marsh crab feeding is somewhat independent of light and tidal cycles. Ovigerous females almost never fed. Both diet and feeding activity of this crab seem to be flexible traits adapted to different combinations of physical and biological factors.